Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1029/2006ja012199
|View full text |Cite
|
Sign up to set email alerts
|

Climatology of the equatorial thermospheric mass density anomaly

Abstract: [1] The equatorial anomaly is an interesting and important feature of the Earth's thermosphere-ionosphere coupling in tropical regions. It is an anomalous latitudinal distribution found in both the ionized and unionized part of the atmosphere. Its equinox configuration consists of a minimum near the dip equator flanked by two maxima on both sides. The ionospheric side of this anomaly, often referred to as the equatorial ionization anomaly (EIA), has long been recognized since the 1930s. However, its thermosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
166
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(200 citation statements)
references
References 32 publications
31
166
3
Order By: Relevance
“…11a) increases from the winter pole to the summer pole with amplitude ∼40%; at equinoxes, the density exhibits little latitudinal variations. The large latitudinal gradient of neutral density at solstices and small latitudinal gradient of neutral density at equinoxes are consistent with the overall latitudinal distribution of neutral density observed by CHAMP (Liu et al 2007b). However, Liu et al (2007b) found the anomalous latitudinal variation of neutral density, the "equatorial mass anomaly" (EMA) in CHAMP density, with neutral mass density showing a dip at the magnetic equator and two crests on each side.…”
Section: Latitudinal Variationsupporting
confidence: 70%
See 2 more Smart Citations
“…11a) increases from the winter pole to the summer pole with amplitude ∼40%; at equinoxes, the density exhibits little latitudinal variations. The large latitudinal gradient of neutral density at solstices and small latitudinal gradient of neutral density at equinoxes are consistent with the overall latitudinal distribution of neutral density observed by CHAMP (Liu et al 2007b). However, Liu et al (2007b) found the anomalous latitudinal variation of neutral density, the "equatorial mass anomaly" (EMA) in CHAMP density, with neutral mass density showing a dip at the magnetic equator and two crests on each side.…”
Section: Latitudinal Variationsupporting
confidence: 70%
“…In this simulation with constant solar minimum forcing, neutral density near March equinox is higher than the September equinox by ∼14%. This equinoctial asymmetry, with neutral density near March equinox being higher than that near the September equinox, is also observed by the CHAMP (Liu et al 2007b;Müller et al 2009). Furthermore, O number density shows similar annual/semiannual variations compared to the neutral density (Figs.…”
Section: Latitudinal Variationmentioning
confidence: 69%
See 1 more Smart Citation
“…The model densities are taken from the NRLMSISE-00 atmospheric model (Picone et al, 2002). Since the CHAMP orbit altitude varies roughly within one scale height (H ≈60 km), errors caused by the normalisation are expected to be small: Liu et al (2007) quoted an uncertainty of 5%. This is regarded acceptable, when comparing a multi-year period over which the spacecraft decays by about 65 km.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…Neutral density depletions (NDDs) at low magnetic latitudes were first has an electrostatic accelerometer which measures the non-gravitational ac-68 celeration precisely (Lühr et al, 2004;Liu et al, 2007). Neutral mass density 69 with the time rate of 10 second is calculated from the accelerometer data.…”
mentioning
confidence: 99%